A literatura de cordel como instrumento didático-pedagógico no processo ensino-aprendizagem de química no ensino médio integrado - Oliveira Neto, Nilton Azevedo de (2020)
The present work is characterized as the continuation and deepening of a study started in 2016. This development is part of the research line Educational Practices in Professional and Technological Education and purpose of presenting Cordel Literature as a method of studying Chemistry in Integrated High School. Through a qualitative approach, research was used bibliography and action research as technical procedures. The latter was carried out with EMI students to the last phase of the action plan, and evolved the elaboration and application of the Educational Product, consisting of two corded e-books on the history and current organization of the Periodic Table, respectively. The second moment of the research with the participation of ten Chemistry professors from different campuses of the Institutes Federal, a phase that aimed to evaluate the Educational Product. As data collection instrument, two questionnaires were used, one of a diagnostic character, another of an evaluative nature, both applied remotely. For data analysis bibliographic analysis, Categorical Analysis was used, one of the techniques that make up Content by Laurence Bardin. In the corpus of bibliographic research on the use of cordel as a study method, the categories were identified, established a priori, used to guide the elaboration of the questionnaires. After analyzing the educational product, 80% of teachers classified it as a good motivational study strategy; 50% indicated not as a good strategy to address content considered more difficult; 100% they considered it a good method for approaching the history and philosophy of science; 100% saw it as a good means of producing and disseminating knowledge by students; 100% saw it as a good strategy to involve students in events scientific and / or cultural; 50% agree that it can be a good initiation strategy search; and, finally, 100% indicated that they would both use and recommend the use of product. This proposal is expected to contribute to the dialogue between science and art, technology and culture, in the teaching-learning process, with a view to the integral training of human beings.